(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2017)
Jatropha curcas Linn. is a multipurpose plant in the Euphorbiaceae family. Numerous reports have indicated the antioxidant properties of phenolics and flavonoids present in J. curcas root methanolic extract. In the present study, 80% methanolic extract of J. curcas root was prepared and used for extraction of bioactive compounds with five solvents (hexane, chloroform, ethyl acetate, n-butanol and water) by liquid-liquid fractionation. The fractions were evaluated for total phenolic content (TPC), total flavonoid content (TFC) and antioxidant activities by using the 2-2’-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing/antioxidant potential (FRAP) and 2,2′-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS) assays. The phytochemical compounds present in each fraction were identified by liquid chromatography mass spectrometry (LCMS) analysis. The TPC of ethyl acetate and n-butanol fractions were 34.0 ± 0.02 μg GAE/g DW and 33.1± 0.01 μg GAE /g DW, respectively, while the TFC were 9.2 ± 0.04 μg CE/g DW and 10.1 ± 0.01 μg CE/g DW, respectively. The free radical scavenging activity varied with the solvents used. Ethyl acetate fraction showed the highest inhibition for DPPH (48.7%) and FRAP (79.6%) assays, while n-butanol fraction showed the highest ABTS radical scavenging activity (94.8%). The LCMS analysis showed the compounds present in the various fractions were phenolic and flavonoid derivatives such as coumaric acid, epigenin, quercetin, leuteolin and pcoumaroylquinic acid. The results showed that TPC, TFC and antioxidant activity for ethyl acetate and n-butanol fractions were higher compared to the other solvent fractions.